Juegos tradicionales y convivencia escolar en niños de preparatoria, Escuela de Educación Básica Luis Antonio Erique Ortega, ciudad de Loja, periodo 2023-2024 - Encarnación Medina, Paola Carolina (2024)
School coexistence is a means of social integration that enhances the infants’ integral development and has a significant impact on their academic performance. This paper was aimed to determine how traditional games influence the school coexistence of children in primary school at the Luis Antonio Erique Ortega Basic Education School in the city of Loja. For the research development, a methodology with a quasi-experimental design, descriptive scope and mixed approach was used, which allowed the collection and analysis of qualitative and quantitative data; the methods used were inductive-deductive and analytical-synthetic. The study comprised a sample of 17 children to whom the SENA test (Evaluation System for Children and Adolescents by its acronyms in Spanish) was applied. The results verified that 88% of the children were at a low level of coexistence, presenting problems managing social, emotional and behavioural skills, and that only 12% had an adequate level of coexistence when following instructions, respecting rules, working in groups, among others. In order to contribute to the solution of the problem, it was designed and applied an activity guide based on traditional games. At the end of the intervention, it was demonstrated that its use strengthened the school coexistence of infants, contributing to the development of a healthy school environment, thus demonstrating in the post-test that 88% of children with living problems decreased to 59%, and the adequate level of coexistence increased to 41%. Finally, it is concluded that traditional games used as a pedagogical strategy allow children to improve their interpersonal relationships, promote assertive communication, follow instructions, rules and turns, and above all, promote teamwork and collaboration, improving and strengthening academic learning. Key words: Social skills, games, rules of coexistence, emotional problems, behavioural, interpersonal relationships.